Addition of Saturated and Trans-fatty Acids to the Diet Induces Depressive and Anxiety-like Behaviors in Drosophila melanogaster. (1st September 2020) - Meichtry, Luana Barreto; Poetini, Márcia Rósula; Dahleh, Mustafa Munir Mustafa; Araujo, Stífani Machado; Musachio, Elize Aparecida Santos; Bortolotto, Vandreza Cardoso; de Freitas Couto, Shanda; Somacal, Sabrina; Emanuelli, Tatiana; Gayer, Mateus Cristofari; Roehrs, Rafael; Guerra, Gustavo Petri; et al.
Highlights: Hydrogenated vegetable fat and lard reduce serotonin and octopamine levels in head of flies. Hydrogenated vegetable fat and lard induce depressive-like and aggressive behavior in flies. Hydrogenated vegetable fat induces anxiety-like behavior in flies. Composition of the fatty acids in diet can influence the signaling of neurotransmitters. Behavioral changes correlate with reduction in serotonin and octopamine levels. Abstract: This study aimed to evaluate the effects of the addition of saturated fat and hydrogenated vegetable fat (HVF) to the diet on depressive and anxiety-like behaviors in Drosophila melanogaster. Flies were exposed to experimental diets: regular diet (RD), or HVF in the concentrations of the substitute (SHVF), HVF 10% and HVF 20%, or Lard (L) in the concentrations of the substitute (SL), L 10% and L 20%, during seven days. Our results showed that flies fed with the HVF diet presented similar behaviors to depression, anxiety, and a higher number of aggressive events. Flies exposed to L showed only depressive-like behavior. Regarding serotonin levels (5HT), there was a significant reduction in the flies exposed to SHVF, HVF 10%, HVF 20%, and L 20%. Regarding the levels of octopamine (OA), there was a significant reduction in the flies exposed to both HVF and L rich diets when compared with the RD group. Also, there was a significant negative correlation between 5HT or OA levels and behaviors of aggressiveness, negative geotaxis, immobility time, light/dark, and grooming in the flies. This study shows that D. melanogaster can serve as a valuable model for understanding psychiatric disorders and that the type of fatty acid (FA) offered in the diet can influence these disorders. This demonstrates the importance of the composition of the FAs in the neural pathways, being able to influence the signaling of neurotransmitters, such as 5HT and OA, and thus, cause behavioral changes.